Clarifying absorptive capacity and dynamic capabilities dilemma in high dynamic market IT SMEs. Issue 3 (12th August 2019) - Senivongse, Chulatep; Bennet, Alex; Mariano, Stefania
Abstract : Purpose: The purpose of this study is to investigate absorptive capacity and dynamic capabilities dilemma in high dynamic market IT small medium enterprises (SMEs). Absorptive capacity and dynamic capabilities have a conflict in theoretical stance. Those in favor of dynamic capabilities regard absorptive capacity as a part of dynamic capabilities, and there are many arguments regarding treating absorptive capacity as a part of dynamic capabilities. One major deficit of dynamic capabilities is that it requires adjusting the firm's dynamic resources when responding to change, requiring some investment and time. Thus, dynamic capabilities then have a problem in instantaneously responding to a highly dynamic market. With the requirement to adjust organizational resources, absorptive capacity, as a part of dynamic capabilities, cannot have direct impact on a firm's performance. Design/methodology/approach: To show that absorptive capacity, by itself, can have a direct impact on a firm's performance in a highly dynamic market, quantifiable variables are identified to measure the level of effort in developing absorptive capacity. The relationships between the absorptive capacity development effort and the firm's financial performance is then explored and evaluated. Findings: It is confirmed that absorptive capacity in a high dynamic market such as IT SMEs have direct and positive impact to the firm's financial performance, without having to configure its resource to interact with changes. Originality/value: The study discusses the paradoxical dilemma of the role of absorptive capacity under the light of dynamic capability. The finding indicates that in high dynamic market when the spontaneous respond to market change is crucial to firm's survival, absorptive capacity can direly deliver the result to leverage the firm's performance without having to reconfigure its resources as indicated in the theoretical stance of dynamic capability.